Ethane Pyrolysis in a Tubular Reactor Using a Modified Computer Solution of Differential Equations System - A. Youssef, Nadia (Asian Journal of Chemistry, 2010)
In this paper the pyrolysis of ethane in a tubular reactor is represented essentially by irreversible first order chemical reaction. The required thermodynamic properties, kinetic information and physical constants are given. The steady state material and energy balances are established. We derived a system of two differential equations describing the axial temperature and conversion profiles for pyrolysis of ethane in a tubular reactor. It is required to calculate the length of tube for producing a desired maximum conversion of decomposition of ethane to ethylene and hydrogen. A modified method, which is numerically stable and convergent, is applied for solving the differential equations system. A computer flow-chart is constructed and represented in a computer FORTRAN IV program for solving the problem. The program has been run using the parameters given with several different values for the length increment and the internal diameter of reactor tube. The total reactor length and the temperature at the reactor outlet corresponding to the desired maximum conversion of ethane are explicitly calculated.